Protein Patterns in Arbuscular Mycorrhizal Roots and Non-Mycorrhizal Roots of Oil Palm Seedling - HAPPY WIDIASTUTI; NAMPIAH SUKARNO; LATIFAH KOSIM DARUSMAN (Microbiology Indonesia, 2007)
A comparison of the protein patterns in root extracts from none mycorrhizal and mycorrhizal oil palm roots has been made. The polypeptides were analyzed every three weeks up to 11 weeks. A factorial design of fungi species (no mycorrhizal, Acaulospora tuberculata, Gigaspora margarita) and with or without fertilizer was assessed. The result showed that specific polypeptides were detected in primary and secondary roots. In unfertilized oil palm root, a 60 kDa polypeptide was detected while it was abcent in fertilized root. Inoculation of A. tuberculata with the addition of fertilizer application yielded a specific 26.7 kDa polypeptide in primary root on the 11th week after inoculation. A specific 64.2 kDa polypeptide of G. margarita was detected in unfertilized secondary root also on the 11th week.